Quantitative Safety Analysis of Train Control System Considering Common Cause Failure - LUO Jiguang (Kongzhi Yu Xinxi Jishu)
The train control system, a safety-related component pivotal for ensuring the operational safety of trains, is prone to causing common cause failures (CCF) due to its multi-channel redundancy design. Hence, it is necessary to conduct a CCF analysis and implement safety protection for the train control system. Based on the system safety theory, potential common cause failures within the system were analyzed and evaluated using factor and independence analysis methods, and weak links were identified and examined in the system design process through a common cause failure checklist, leading to the proposed safety protection measures. Moreover, a quantitative evaluation was conducted on common cause failures based on a factor model to determine whether the probability of dangerous failure of the system within the acceptable range and aligns with the specified safety objectives. The article takes the computer interlocking system as the research object, and the quantitative calculation results indicated a reduced impact of common cause failures with a smaller factor. Consequently, it is recommended to incorporate appropriate safety protection measures in the system design to minimize the probability in the occurrence of common cause failures. By decreasing the factor value used in estimating system failures resulting from common cause failures, system safety is improved.